2021
DOI: 10.1136/bmjdrc-2020-002085
|View full text |Cite
|
Sign up to set email alerts
|

Orai–vascular endothelial-cadherin signaling complex regulates high-glucose exposure-induced increased permeability of mouse aortic endothelial cells

Abstract: IntroductionDiabetes-associated endothelial barrier function impairment might be linked to disturbances in Ca2+ homeostasis. To study the role and molecular mechanism of Orais–vascular endothelial (VE)-cadherin signaling complex and its downstream signaling pathway in diabetic endothelial injury using mouse aortic endothelial cells (MAECs).Research design and methodsThe activity of store-operated Ca2+ entry (SOCE) was detected by calcium imaging after 7 days of high-glucose (HG) or normal-glucose (NG) exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…When NFATC1 translocates from the cytosol to the nucleus, it can bind to gene promoter regions and induce the expression of numerous genes ( 29 ). Therefore, we next investigated the role of the calmodulin/calcineurin/NFATC1 signaling pathway on the regulation of COL1A1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When NFATC1 translocates from the cytosol to the nucleus, it can bind to gene promoter regions and induce the expression of numerous genes ( 29 ). Therefore, we next investigated the role of the calmodulin/calcineurin/NFATC1 signaling pathway on the regulation of COL1A1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, many studies have indicated that SOCErelated proteins, including Orais and STIM1, affect the vascular system in a variety of pathological conditions. The Orai1 protein, which is located in the endothelial cell plasma membrane, is involved in various dysfunctions of the endothelium (12,(29)(30)(31). For example, Orai1 and STIM1 mediate histamine-induced endothelial inflammation, and Orai1 is involved in endoplasmic reticulum stress-induced endothelial dysfunction (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of TRPV4 caused an increase in the intracellular Ca 2+ concentration through influx of extracellular Ca 2+ , triggering an event which is accompanied by a downregulation of the tight junctional proteins claudin -1, -3, -4, -5, -7, and -8 and by dramatic changes in tight junction morphology, including frequent large breaks in the tight junction strands [ 26 ]. In addition, calcium/calmodulin-dependent protein kinase can enhance the phosphorylation of adhesin proteins such as VE-cadherin and resulting in disruption of epithelial cell junctions [ 27 ]. The activation of TRPV4 in the gastrointestinal tract causes experimental colitis in mice, which also causes the downregulation of claudin-7 and changes in tight junction morphology [ 22 ].…”
Section: Discussionmentioning
confidence: 99%